An evaluation of a multi‐component intervention for loud speech among children with autism spectrum disorder. (17th January 2023) - Spinks, Hailey M.; Falcomata, Terry S.; Spinks, Elissa M.
Abstract: Idiosyncratic patterns of speech are common among individuals with autism spectrum disorder (ASD) and can greatly affect their ability to participate successfully in various social and educational settings. We evaluated a treatment package with three children with ASD and a history of loud speech. A multiple baseline across participants design and a decibel meter application were used to evaluate whether the multi‐component intervention (i.e., a rule, differential reinforcement, and in vivo feedback) would effectively reduce participants' rates of loud speech. The results showed that the intervention decreased rates of loud speech for all participants. Results are discussed in terms of (a) their extension of the literature regarding speech prosody in ASD by demonstrating an effective intervention for loud speech, (b) clinical implications, and (c) potential future research regarding this nuanced, yet crucial aspect of social communication, including appropriate methods for addressing loud speech in individuals with ASD.